Social Disorganization and Neighborhood Crime in Argentine Shantytowns - Miguez, Daniel Pedro (2014)
This study analyzes the effects of conflictive social networks on a particular form of neighborhood crime called ‘street harassment’ in Argentine shantytowns. The data for the study is provided by a victimization survey applied in six Argentine cities, comparing the association between crime and neighborhood cohesion in different social strata. The study is based on social disorganization theory, but it adds two new insights to this perspective by exploring the role of political leadership and culture. Its main conclusion is that while conflictive social networks are strongly associated with neighborhood crime, these are concentrated in small numbers of shantytown dwellers. In addition, results also reveal that ambivalent attitudes towards conventional social principles and lack of trust in local political leadership are associated with neighborhood conflicts and crime.